Surgical Management of Submandibular Gland Sialolithiasis: A Case Report - Portela, Davi Barbosa; Ferreira Filho, Josfran da Silva; Sampaio, Eduardo Ribeiro; Salgado Piato Souza, Bruna; Escobar, Larissa Betina Alves; Melo, Radamés Bezerra; Martins, Maria Fabiane Parente (Brazilian Journal of Case Reports, 2025)
Sialolithiasis is an inflammation caused by the obstruction of a salivary gland’s excretory system due to the formation of calculi. These mineralized structures occur mainly in the major salivary glands, particularly in the submandibular gland, due to the higher viscosity of saliva and increased concentrations of calcium and phosphate. The formation of sialoliths involves factors such as low salivary flow, infections, dehydration, and pH alterations, which lead to solute crystallization. Treatment aims to remove the sialolith; when the calculus is small and located near the duct opening, duct dilation and gland massage may result in its expulsion. However, if these conditions are not met, surgical removal becomes necessary. This case report describes a 26-year-old patient who presented to an Oral Surgery service with persistent pain in the submandibular region caused by a sialolith. Despite the absence of radiographic examination, the presence of a calculus in the submandibular duct was confirmed clinically. Surgery was performed under local anesthesia, resulting in successful removal of the sialolith. Postoperative medication and care instructions were provided. Despite the prolonged nature of the condition, the treatment yielded satisfactory results, with no signs of complications or recurrence.